D'Arcy Island - Gill, Don (InTensions, 2008)
“British Columbia has a leper colony. Its existence is not widely known, for those who compose it are of a race whose affairs never reach the public ear.”The Dominion Medical Monthly: Ontario Medical Journal, No. 6, Vol. XI, Toronto, December, 1898. In the nineteenth century D’Arcy Island, a small island off the east coast of Vancouver Island was used by the city of Victoria to quarantine residents diagnosed with leprosy after the discovery of the disease in a few people in 1891. The exhibition D’Arcy Island is part of a larger project, Carceral Landscape, which is concerned with the use of landscape as a device for human incarceration. The idea of Carceral Landscape was germinated by photographer Ansel Adams’s belief that the sublime beauty of the natural environment surrounding the internment camp at Manzanar, California inspired and helped Japanese American internees transcend their detention during WWII. D’Arcy Island critically considers the use of an island as a site of detention or banishment. “While the floor of the Owens Valley is desolate, very hot in summer and very cold in winter, the surrounding mountains are spectacular, especially the Sierra Nevada on the west, culminating in Mount Whitney rising fourteen thousand five hundred feet above the valley floor. The Inyo Range to the east is more of desert character and of lower elevation but is very beautiful in its own way. I have been accused of sentimental conjecture when I suggest that the beauty of the natural scene stimulated the people in the camp. No other relocation centre could match Manzanar in this respect, and many of the people spoke to me of these qualities and their thankfulness for them.”Ansel Adams: an Autobiography. Little Brown, 1998. Pg 220 D’Arcy Island was exhibited at the Southern Alberta Art Gallery in Lethbridge Alberta in Fall 2006. For more information on Don Gill and his work see Don Gill’s website